Peningkatan Aktivitas Belajar Siswa Melalui Metode Kerja Kelompok Dengan Bantuan LKPD di Aplikasi Whatsapp Pada Kelas IX Semester Ganjil SMP Negeri 2 Bintan TA 2020/2021 - Helda Veronica Sipayung (Universitas Muhammadiyah Gresik, 2021)
The purpose of this study is to: to find out how much increase in learning activities occurs after using the group work method with the help of LKPD in the WhatsApp application in online learning. This research is a class action research (PTK). The subjects of this study were students of class IX D SMP Negeri 2 Bintan with 34 students. The object in this study is the mathematics learning activity of students of class IX D SMP Negeri 2 Bintan in the 2020-2021 academic year on quadratic equation material. The data collection technique in this study was carried out by observing the activities carried out by students during the online learning process. The data analysis technique was carried out by calculating the average percentage of student activities. The learning process uses the guided discovery learning model with a scientific approach and discussion method. Early in the learning process, the teacher prepares students to carry out group discussion activities to solve problems in the prepared LKPD. After the students finished discussing in groups, then each group presented the results of the discussion in front of the class. At the end of each lesson, students are asked to do an evaluation that is done individually. The evaluation score obtained by the students was then calculated for the class average and the number of students who reached the KKM score. The results showed that after the use of LKPD through WhatsApp in mathematics learning, there was an increase in student activity from cycle 1 to cycle 3. In cycle 1, the percentage of student activity was 41.17%, in cycle 2 it reached 58.97% and in cycle 3 reached 76.07%. It is suggested for further mathematics learning to use LKPD through WhatsApp on other materials as an alternative source of learning for students so that students' learning activities increase.